Health-Related Quality of Life and Its Influencing Factors in Patients with Hepatitis B: A Cross-Sectional Assessment in Southeastern China - Ping Chen; Fen Zhang; Yiqun Shen; Yubo Cai; Chaolei Jin; Yan Li; Mingmin Tu; Weizhen Zhang; Yu Wang; Shi-Feng Zhang; Jiangyun Wang; Lanjuan Li (Canadian Journal of Gastroenterology and Hepatology)
Health-related quality of life (HRQoL) is an important aspect in the management of patients with hepatitis B (HB), which remains a serious health problem in China. There have been relatively few HRQoL studies involving Chinese patients with HB. The aim of this study was to analyze HRQoL in patients diagnosed with HB living in Zhejiang Province, China. A cross-sectional sample of 98 patients with chronic HB (CHB), 56 patients with advanced HB that have developed cirrhosis, and 48 healthy controls (HCs), all from Zhejiang Province, was used in this study. HRQoL was assessed using Short-Form 36 (SF-36) version 2, European quality of life questionnaire-5 dimensions (EQ-5D), and chronic liver disease questionnaire (CLDQ). Intergroup score differences were detected with U tests. Factors with a significant effect on HRQoL were identified with Spearman correlational analyses. Patients with HB (both groups) had lower SF-36 scores than HCs (p<0.01), with the exception of general health subscores. Patients with HB cirrhosis had the lowest scores in the EQ-5D visual analog scale (VAS) component. Furthermore, patients with HB cirrhosis had lower (p<0.01) CLDQ scores than patients with CHB. In our HB patient cohort, disease stage and income level were the factors most associated with HRQoL variables; age, education level, and marital status were, each, also significantly associated with some HRQoL variables in patients with HB in our study (p<0.05 or p<0.01). HRQoL is diminished in patients with HB in southeastern China. Disease stage and income emerged as key determinants of HRQoL scores. Augmenting social and medical supports for patients with HB, especially those with a socioeconomic status and an advanced disease stage, may help to enhance HRQoL.